Uji Aktivitas Antioksidan Ekstrak Etanol 70% Buah Belimbing Wuluh (Averrhoa bilimbi L.) Menggunakan Metode DPPH: Antioxidant Activity Test of Ethanol Extract of 70% Star Fruit (Averrhoa bilimbi L.) Using the DPPH Method - M Herwanda Perdana Kusuma; Aditya Noviadi Rakhmatullah; Azmi Yunarti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Antioxidants are compounds that are able to stabilize free radicals in the body. Free radicals are highly reactive molecules because they have unpaired electrons so that they can interact with the molecules of the body's cells. One of the plants that has properties as an antioxidant for star fruit (Averrhoa bilimbi L.) Star fruit is one of the species in the genus Averrhoa. The purpose of this study was to find out what are the active compounds contained in ethanol extract of 70% star fruit (Averrhoa bilimbi L.) and to determine the antioxidant activity in ethanol extract of 70% star fruit (Averrhoa bilimbi L.) extracted by the maceration method. In this study using the DPPH method. The selection of antioxidant activity testing using the DPPH radical suppression method is due to its easy, simple, fast and sensitive work in evaluating antioxidants from natural ingredient compounds. Based on the results of the study qualitatively ethanol extract 70% star fruit (Averrhoa bilimbi L.) contains secondary metabolite compounds flavonoids, alkaloids, saponins, and terpenoids and quantitatively has an IC50 value of 74,625 ppm which is included in the category of strong antioxidants.